Right trisectionectomy for liver metastasis of granulosa cell tumor: a case report and literature review - Itsuki Koganezawa; Koichi Tomita; Masashi Nakagawa; Yosuke Ozawa; Toshimichi Kobayashi; Toru Sano; Rina Tsutsui; Naokazu Chiba; Akira Okimura; Munehide Nakatsugawa; Hiroshi Hirano; Shigeyuki Kawachi (Surgical Case Reports)
Abstract Background Granulosa cell tumor (GCT) is a type of ovarian sex cord-stromal tumor with low-grade malignancy, which can recur long after primary resection. All reports on GCTs in the liver describe cases of metastases, while there are no previous reports of primary GCTs originating from the liver. We report a case of GCT, with recurrence of liver metastasis long after ovariectomy, which was subsequently resected by a right trisectionectomy. Case presentation A 76-year-old woman presented with a history of surgical resection of an ovarian tumor performed 30 years previously; no details of the tumor were available. When she was 68 years old, an abdominal ultrasound revealed a small liver mass, which was diagnosed as a hepatic hemangioma with slow growth. Outpatient follow-up was discontinued for 5 years, and the patient was not examined again until the age of 76 years. At this point, the tumor had substantially increased in size, and surgical resection was required owing to suspicion of malignancy. The patient was then referred to our hospital. Contrast-enhanced computed tomography (CT) showed a large tumor, approximately 18 cm in size, occupying the right lobe and medial section of the liver. After percutaneous transhepatic portal vein embolization, a right trisectionectomy was performed. The histopathological findings of the resected specimen showed that the tumor cells had “coffee bean-like” nuclear grooves, which are characteristic of a GCT. Acidophilic non-structural Call-Exner bodies were also observed. Inhibin-α, CD99, and CD56 markers of sex cord-stromal tumors were detected on immunohistological examination; all pathology suggested a GCT. We considered the tumor to be a liver metastasis of a previous ovarian GCT that was resected 30 years prior by ovariectomy. There was no recurrence for > 15 months after the hepatectomy. Conclusions We report a case of a GCT in the liver, which was identified to be a liver metastasis. Right trisectionectomy was subsequently performed for tumor resection. Clinicians should be aware that ovarian GCTs may recur in the liver, and that GCT recurrence may occur long after ovariectomy of the primary ovarian GCT.